A Resistance against Colonialism: Thematic and Lexical Analysis of M. R. Gohar’s Poetry: A Corpus Assisted Approach - Arooj, Sadaf; Abbas, Ghulam (Pakistan Languages and Humanities Review, 2025)
The study aims to expand the analysis of English poetry employing indigenous lexicons and themes that acts as hidden resistance against colonial hegemony. Power of words cannot be underestimated. History shows that regional expressions in manuscripts act as a shield against the silent systems of supremacy. Braun & Clarke’s thematic analysis and manual discourse analysis are conducted on Muhammad Riaz Gohar’s English poetry. Gohar’s choices between a dominant language and an obscure vernacular with having its strong cultural display are screened through AntConc 4.3.2. Local perspectives, terminologies and cultural exhibition in external dominant speech systems serve as a covert indicator of dissent. He softly confronts dominant colonial discourses through preserving its cultural identity and regional diction. It is the continuity of the work of marginalized communities retains strength by presenting their culture on global literary landscape. The study recommends to explore assimilation of imperial doctrines in local literary work.